Encountering Nazi tourism sites - Dalton, Derek (Routledge advances in tourism, 2020)
Introduction : surveying the Holocaust tourism memorial field in Germany -- Profane splendour : the Wannsee House -- The topography of terror : the foundations of Nazi rule -- Wewelsburg Castle : against an SS phantasia -- The Anne Frank House/Museum -- Concentration camp tourism in Germany : two encounters -- The Jewish Museum Berlin : encountering trauma -- Berlin Holocaust memorials : marking past atrocity in the space of the city -- Conclusion : Nazi crime-related tourism in contemporary Germany.